Pharmacokinetic Profile and Antihyperlipidemic Effectiveness of Nanoemulsion and Ethanol Extract of Parang Romang (Boehmeria virgata) Leaves: Profil Farmakokinetik dan Efektifitas Antihiperlipidemia Sediaan Nanoemulsi dan Ekstrak Etanol dari Daun Parang Romang (Boehmeria virgata) - Magfirah Magfirah (Universitas Tadulako, 2022)
Background: Parang romang (Boehmeria virgata) has an antihyperlipidemic effect, but the use of herbs commonly has limitations with poor solubility in water, causing failure in the clinical phase due to low bioavailability. Bioavailability can be increased by nanotechnologies, one of them is nanoemulsion. Objectives: This study aimed to determine the pharmacokinetic profile and effectiveness of antihyperlipidemic activity of nanoemulsion preparation and ethanol extract of parang romang leaves. Methods: Pharmacokinetic study was done with 10 rats that each given 100 mg/kg BW of nanoemulsion and ethanol extract from parang romang leaves. The blood was taken at 0.5; 1; 1.5; 2; 2.5; 3; 3.5; 4 hours to measure tmax, Cpmax, and AUC. Study of antihyperlipidemic was done with 30 rats divided into 5 groups with normal control group I given Na CMC suspension, group II negative control given high fat feed + streptozotocin, group III positive control given high fat feed + streptozotocin and simvastatin 0.9 mg/ kg BW, group IV given high fat feed + streptozotocin + ethanol extract of parang romang leaves 100 mg/kg BW and group V given high fat feed + streptozotocin + nanoemulsion of ethanol extract of parang romang 100 mg/kg BW. The blood was then taken on day 0,14,21, 28 and 35. Results: The results of the pharmacokinetic profile test showed that the values ​​of tmax, Cpmax, and AUC for nanoemulsions and extract were respectively; 0.5 hours, 96.68 g/ml and 297.57 and 1-hour, 15.44 g/ml and 93.53. The statistical results obtained a significant value (P < 0,05) which showed a significant effect between nanoemulsion and ethanol extract of parang romang to reduce cholesterol levels Conclusions: There are differences in pharmacokinetic profile and antihyperlipidemic effectiveness between nanoemulsion preparations and ethanol extracts from parang romang leaves.